2023
DOI: 10.1099/ijsem.0.005844
|View full text |Cite
|
Sign up to set email alerts
|

AppIndels.com server: a web-based tool for the identification of known taxon-specific conserved signature indels in genome sequences. Validation of its usefulness by predicting the taxonomic affiliation of >700 unclassified strains of Bacillus species

Radhey S. Gupta,
David A. Kanter-Eivin

Abstract: Taxon-specific conserved signature indels (CSIs) in genes/proteins provide reliable molecular markers (synapomorphies) for unambiguous demarcation of taxa of different ranks in molecular terms and for genetic, biochemical and diagnostic studies. Because of their predictive abilities, the shared presence of known taxon-specific CSIs in genome sequences has proven useful for taxonomic purposes. However, the lack of a convenient method for identifying the presence of known CSIs in genome sequences has limited the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 110 publications
(350 reference statements)
2
3
0
Order By: Relevance
“…Earlier work on CSIs specific for different taxonomic groups has shown that these molecular characteristics exhibit a high degree of predictive ability to be found in other members (newly identified or sequenced) of these taxa [27,47,48,60]. This inference is also supported by the results presented here where several unnamed Peptostreptococcaceae species that shared CSIs specific for a given genus/clade were found to branch reliably with its members.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…Earlier work on CSIs specific for different taxonomic groups has shown that these molecular characteristics exhibit a high degree of predictive ability to be found in other members (newly identified or sequenced) of these taxa [27,47,48,60]. This inference is also supported by the results presented here where several unnamed Peptostreptococcaceae species that shared CSIs specific for a given genus/clade were found to branch reliably with its members.…”
Section: Discussionsupporting
confidence: 86%
“…9), the strains of all uncharacterized species, which shared the CSIs specific for a given clade, branched reliably with the named species from that clade. These results provide further evidence supporting the contention that the identified CSIs are highly specific characteristics of the observed clades and their shared presence in an uncharacterized species is strongly indicative of a close relationship with that specific clade [47,48,53].…”
Section: Predictive Ability Of the Shared Csis For Taxonomic Affiliationsupporting
confidence: 80%
See 3 more Smart Citations